Policy & social work practice - Evans, Antony; Keating, Frank (SAGE, 2016)
Editors Evans and Keating present readers with a collection of academic essays designed to allow for critical thinking regarding the relationship between policy and practice in social work. The editors argue that social policy is central to social work practice. The ten contributions that make up the text focus on discretion in history and the development of social work, social work education and training as a policy issue, the development of safeguarding in children's services, and many other related subjects. The editors are both faculty members of the University of London in the UK.